Digital Storytelling for Vocational Students’ Speaking and Writing Skills - Palupi, Elvina Anggraeni Retno; ZULIKHATIN NUROH, ERMAWATI (Indonesian Journal of Education Methods Development, 2025)
General background: The rapid advancement of technology has transformed educational practices, providing new opportunities for integrating digital media into language learning. Specific background: Despite its growing use, the role of digital storytelling in fostering students’ speaking and writing skills in vocational education remains underexplored. Knowledge gap: Previous studies have highlighted digital tools in language learning, yet limited evidence exists on how vocational high school students perceive and experience digital storytelling as a medium for English learning. Aims: This study investigates tenth-grade vocational students’ perspectives on using digital storytelling to develop speaking and writing skills. Results: Data collected through interviews, video analysis, and observation revealed that digital storytelling fosters creativity, improves fluency in oral communication, enriches vocabulary, and strengthens writing competence. Students also reported increased confidence and readiness to integrate digital media into their learning practices. Novelty: Unlike prior research that employed multiple complex tools, this study demonstrates the practical use of accessible applications (Canva and CapCut) for creating effective storytelling media. Implications: Findings suggest that digital storytelling can serve as a practical and motivating pedagogical approach for enhancing vocational students’ literacy skills while preparing them for technology-oriented learning environments. Highlights: Explores vocational students’ perspectives on digital storytelling in English learning. Shows improved speaking and writing skills through creative multimedia use. Demonstrates practical application of simple tools (Canva, CapCut) in education. Keywords: Digital Storytelling, Vocational Education, Speaking Skills, Writing Skills, Language Learning